2011
DOI: 10.1017/s0954422411000047
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal gene expression in pigs: effects of reduced feed intake during weaning and potential impact of dietary components

Abstract: The weaning transition is characterised by morphological, histological and microbial changes, often leading to weaning-associated disorders. These intestinal changes can partly be ascribed to the lack of luminal nutrition arising from the reduced feed intake common in pigs after weaning. It is increasingly becoming clear that changes in the supply with enteral nutrients may have major impacts on intestinal gene expression. Furthermore, the major dietary constituents, i.e. carbohydrates, fatty acids and amino a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 225 publications
0
18
0
Order By: Relevance
“…We suggest that this characteristic contributes to decrease the distance between the intestinal lumen and the lamina propria, thus shortening the distance of the trajectory followed by nutrients from the lumen toward blood and lymphatic capillaries. This hypothesis is corroborated by the increase in the transcription of brush border membrane transporters in the enterocytes of rats submitted to DR (Bauer et al, 2011). It is worth emphasizing that the duodenum has a crucial role for the food digestion and especially the apical portion of duodenal enterocytes contains enzymes that finalize the digestion of carbohydrates and peptides.…”
Section: Duodenummentioning
confidence: 69%
See 1 more Smart Citation
“…We suggest that this characteristic contributes to decrease the distance between the intestinal lumen and the lamina propria, thus shortening the distance of the trajectory followed by nutrients from the lumen toward blood and lymphatic capillaries. This hypothesis is corroborated by the increase in the transcription of brush border membrane transporters in the enterocytes of rats submitted to DR (Bauer et al, 2011). It is worth emphasizing that the duodenum has a crucial role for the food digestion and especially the apical portion of duodenal enterocytes contains enzymes that finalize the digestion of carbohydrates and peptides.…”
Section: Duodenummentioning
confidence: 69%
“…There are a range of dietary options being studied for elderly individuals and dietary restriction (DR) is one of the main ones recommended (Holt et al, 1998;Grattagliano et al, 2004;Cencic and Chingwaru, 2010;Reimer et al, 2010;Bauer et al, 2011;Arslan-Ergul et al, 2013;Cirilo et al, 2013;Walsh et al, 2013). Studies performed in the 1930s (McCay et al, 1935) reported for the first time that DR promoted an increase of the maximum life span of experimental animals, such as rats and mice.…”
Section: Introductionmentioning
confidence: 99%
“…This could be due to a reduction of food consumption caused by higher secretion of pro-inflammatory cytokines (Bauer et al ., 2011;Parra et al ., 2013). It may also suggest that D3 results are related to a saturation of the recognition receptors that mediate cellular signaling induced by LPS (Gomes et al ., 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Stress during weaning causes functional and structural alterations in small intestine mucosa (SPREEUWENBERG et al, 2001;BOUDRY et al, 2004), induces mucosal inflammatory reactions (MCCRACKEN et al, 1999), and promotes an imbalance in the intestinal microflora (CASTILLO et al, 2007;BAUER et al, 2011), so we can also infer that it plays a major role in defining the piglet FI pattern in the first weeks post-weaning by making pigs less sensitive to nutritional variations, except for those associated with excess protein and amino acids. In addition, the thermal environment also affects the voluntary FI of pigs (COLLIN et al, 2001); however, in the present study, the thermal environment was characterized as thermoneutral, so it should not have affected the piglet FI pattern.…”
Section: Resultsmentioning
confidence: 99%